Etika Artificial Intelligence dalam Perspektif Hadis Nabi: Telaah Filosofis terhadap Relasi Manusia dan Teknologi - Winda Sari (UIN Sumatera Utara, 2026)
The rapid development of Artificial Intelligence (AI) has created significant opportunities while simultaneously raising ethical challenges in various aspects of human life, including misinformation, privacy violations, algorithmic bias, and the diminishing accountability of technology-assisted decision-making. These challenges highlight the need for an ethical framework that is grounded not only in technological considerations but also in strong moral principles. This study aims to analyze the ethical principles of Artificial Intelligence from the perspective of the Prophet's Hadith through a philosophical examination of the relationship between humans and technology. The research employs a qualitative approach using library research as its primary method. Primary data were collected from authoritative Hadith compilations and their classical commentaries, while secondary data were obtained from literature on Islamic philosophy, technology ethics, official AI ethics documents, and relevant scholarly publications. Data were collected through documentation techniques and analyzed using a descriptive-analytical approach by identifying Hadith related to ethical values, interpreting their meanings through Hadith commentaries, and contextualizing them within Islamic philosophical thought and contemporary AI ethics discourse. The findings reveal four fundamental ethical principles derived from the Prophet's Hadith: trustworthiness and responsibility (amanah), truthfulness and information verification (tabayyun), the prevention of harm (lā ḍarar wa lā ḍirār), and the promotion of public benefit (maṣlaḥah). These principles affirm that human beings remain the primary moral agents responsible for the development and use of AI, whereas AI should function solely as an instrument to promote human welfare and preserve human dignity. This study contributes to contemporary Hadith scholarship by proposing a Hadith-Based AI Ethics Framework, thereby enriching the dialogue between Hadith studies, Islamic philosophy, and modern technology ethics.